Evaluation of the effect of soybean diet on interferon-α-induced depression in male mice - Yazdan Azimi Fashi; Azadeh Mesripour; Valiollah Hajhashemi (Avicenna Journal of Phytomedicine, 2017)
Objective: Interferon-α (IFN) therapy can cause depressive symptom which may lead to drug discontinuation. By interfering with tryptophan pathway, the available level of tryptophan required for serotonin synthesis decreases which could be related to depression. The aim of this study was to evaluate whether soybean diet could improve IFN-induced depression. Materials and Methods: Male mice weighing 28±3 g were used in the forced swimming test (FST) as an animal model of depression; also, locomotor activity was recorded. IFN 16×105 IU/kg was injected subcutaneously for 6 days. Animals were fed with regular diet or soybean diet at 3 concentrations throughout the experiment. Fluoxetine was the reference drug. To check whether the tryptophan content in the soy bean diet was effective, a group of animals was injected with a single dose of tryptophan on the test day. Results: IFN-α increased the immobility time in the FST (192 sec ± 5.4), that denotes depression in mice. Soybean diets caused less immobility that was more profound with 50% soybean (26.4 sec ± 6). This diet overcame the depression caused by IFN in the FST (54 sec±18). This result was parallel with that of tryptophan injected to animals (38 sec±17). All the animals showed normal locomotor activity. Conclusion: For the first time, we showed that soybean diet could counteract with depression caused by IFN-α. Since tryptophan therapy had similar effects, possibly the tryptophan content of soybean had induced the serotonin synthesis. Thus, not only less harmful kynurenine was produced but also more serotonin was available in the brain to overcome depression. However, this interpretation needs further evaluations.